(untitled) (Comprehensive Journal of Science, 2026)
This study examines the concept of the negative administrative decision arising from the non-execution of judicial rulings within the framework of administrative law. It aims to clarify the concept of such decisions, their characteristics and manifestations, and to analyze the legal framework governing their challenge before administrative courts, particularly in terms of jurisdiction, the admissibility requirements of annulment actions, and the grounds for appeal. The study adopts both the analytical method, in interpreting the legal provisions regulating administrative judiciary, and the inductive method, in deriving established principles from judicial rulings. It concludes that the administration’s refusal to execute a final and enforceable judicial ruling constitutes an independent negative administrative decision characterized by its continuous and renewable nature. Such decisions are subject to judicial review before administrative courts, provided that the conditions for appeal are met, whether based on illegality or abuse of power. The significance of this study lies in highlighting one of the most serious forms of negative administrative conduct, given its impact on the authority of judicial rulings and the principle of legality.